A triple carboxylic acid-functionalized RAFT agent platform for the elaboration of well-defined telechelic 3-arm star PDMAc. Issue 9 (15th December 2015) - Belal, K.; Poitras-Jolicoeur, S.; Lyskawa, J.; Pembouong, G.; Cooke, G.; Woisel, P.; Stoffelbach, F.
Abstract : This communication describes the synthesis of a triple acid-functionalized RAFT agent and its use to prepare well-defined 3-arm star polymers of N, N -dimethylacrylamide (DMAc). Abstract : This communication describes the synthesis of a triple acid-functionalized RAFT agent and its use to prepare well-defined 3-arm star polymers of N, N -dimethylacrylamide (DMAc). A simple esterification reaction allowed the convenient integration of three electron-rich naphthalene recognition units on the RAFT agent platform and subsequently the elaboration of a naphthalene end-decorated telechelic 3-arm star PDMAc. This functionalized star polymer was further exploited to build a hydrogel with a complementary homoditopic host unit featuring tetracationic macrocycle cyclobis(paraquat- p -phenylene) units.